Transition from Adult Education to Postsecondary Education - Walston, Tony Dustin (East Carolina University, 2019)
The Workforce Innovation and Opportunity Act (WIOA) that was signed into law in July 2014 by President Barack Obama gave a new identity to adult education programs across the United States. The legislation propelled adult education programs into the college arena like never before. No longer were programs allowed to simply just focus on a high school credential. Instruction that exposed students to career development and real-life application became important. Helping students think about their futures in terms of education and employment also became an important framework for adult education programs. With all of these new considerations, programs across the state of North Carolina began to restructure, redesign, and revisit their mission and vision statements. From these growing pains, programs have continually been searching for the right methods and practices that will position them to be compliant with WIOA. One of the biggest challenges is transitioning students that earn their high school credential into college programs. The Transitional and Career Studies (TCS) program at Lenoir Community College (LCC) produces high school equivalency (HSE/GED) graduates each year, but most never enroll into college programs and take that next step to further their education. The purpose of this study was to determine strategies and best practices that encourage students in the TCS program at LCC to transition into postsecondary education opportunities upon completing their HSE/GED. This action research study design involved implementing a 12- week pilot program that included three classrooms and 23 participants. The participants in the pilot program received contextualized instruction, participated in weekly goal-setting and advising appointments, and had an opportunity for co-enrollment into short-term training programs while working towards their HSE/GED. The findings of this study show an association between the interventions and the participants' educational outcomes.
Keywords: HSE/GED; Adult education--North Carolina--Lenoir County; Postsecondary education--North Carolina--Lenoir County